Time limits: The effects on welfare use and other consumption-smoothing mechanisms - Francesca Mazzolari; Giuseppe Ragusa (Institute for the Study of Labor (IZA), 2012)
We use data from the Survey of Income and Program Participation covering the period 1989-2006 to investigate the impact that time limits on receipt of Temporary Assistance for Needy Families have on female-headed family outcomes, including welfare use, employment and living arrangements. The effects of time limits depend on the stock of remaining months of eligibility, which in turn depends on the state time limit and on family's welfare use since the policy was implemented. Since the latter is potentially endogenous to current outcomes, we form a prediction of remaining eligibility based on state rules and observable family characteristics. For families who are predicted to have hit the limit, we find evidence of enforcement of the policy, which causes monthly income from welfare to drop by an average of 250. This loss is not offset by increases in other income sources: not only there is no significant change in earnings (despite a sizable increase in the likelihood that the mother works), but also income from other transfer programs (such as SSI and Food Stamps) decreases - resulting in increasing rates of deep poverty among these families. Additional analyses suggest that doubling up is a way for families who timed out of welfare to share housekeeping expenses.
Keywords: J20; H53; 330; welfare; time limits; consumption-smoothing; Sozialhilfe; Zeit; Konsumentenverhalten; Anpassung; Privater Haushalt; USA